Oh, Boris! - Weston, Carrie; Warnes, Tim (Oxford : Oxford University Press, 2009)
When a new bear comes to school, all the other animals are afraid of him until he saves them from the Rat Pack bullies.
2.3
K-3.
K-3
Keywords: Animals -- Juvenile fiction; Bears -- Juvenile fiction; Grizzly bear -- Juvenile fiction; Schools -- Juvenile fiction; Animals -- Fiction; Bears -- Fiction; Grizzly bear -- Fiction; Schools -- Fiction; Animals -- Fiction; Bears -- Fiction; Grizzly bears -- Fiction; School stories